Conjunctions Found In Speech “Ivanka Trump 2020 Republican National Convention” - Panjaitan, Bella Natasia; Ambalegin, Ambalegin (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
This research study was to identify the types of conjunction in “Ivanka Trump's 2020 Republican National Convention” speech. The researchers used the theory of the types of conjunction by Halliday & Hasan (1976). This research used a qualitative method that is formed on data and its explanation cannot be measured in numbers by Creswell (2018). This research used a method of observation to collect the data The researchers used the pragmatic identity method by Sudaryanto (2015) to analyze the data in the “Ivanka Trump’s 2020 Republican National Convention” speech. The result of this research showed additive type, adversative type, causal type, and temporal type are identified in the “Ivanka Trump's 2020 Republican National Convention” speech. The type of additive conjunction is dominant in the speech because the speech connects two or more phrases or sentences and the adversative conjunctions are at least type in the speech entitled “Ivanka Trumps 2020 Republican National Convention”. According to the findings, there are a total of 126 data conjunctions, 72 data related to additive conjunctions, 11 data related to adversative conjunctions, 19 data related to causal conjunctions, and 24 data related to temporal conjunctions.